Structural Elucidation of Three Novel Kaempferol O-tri-Glycosides that Are Involved in the Defense Response of Hybrid Ornithogalum to Pectobacterium carotovorum - Iris Yedidia; Keren Schultz; Avner Golan; Hugo E. Gottlieb; Zohar Kerem (Molecules, 2019)
Ornithogalum is an ornamental flowering species that grows from a bulb and is highly susceptible to soft-rot disease caused by Pectobacterium carotovorum (Pc). Interspecific hybridization between O. thyrsoides and O. dubium yielded hybrids with enhanced resistance to that pathogen. The hybrids displayed distinct phenolic-compound profiles with several peaks that were specifically heightened following Pc infection. Three of these compounds were isolated and identified as novel kaempferol O-tri-glycosides. The structures of these compounds were elucidated using reversed phase high-performance liquid chromatography (RP-LC), RP-LC coupled to high-resolution mass spectrometry (RP-LC-MS), and nuclear magnetic resonance (NMR) (1D 1H and 13C, DEPT, HMQC, HMBC, COSY, and NOE), in order to achieve pure and defined compounds data. The new compounds were finally identified as kaempferol 3-O-[4-O-α-l-(3-O-acetic)-rhamnopyranosyl-6-O-β-d-xylopyranosyl]-β-d-glucopyranoside, kaempferol 3-O-[4-O-α-l-(2-O-acetic)-rhamnopyranosyl-6-O-β-d-xylopyranosyl]-β-d-glucopyranoside and kaempferol 3-O-[4-O-α-l-(2,3-O-diacetic)-rhamnopyranosyl-6-O-β-d-xylopyranosyl]-β-d-glucopyranoside.